ESTUDO COMPARATIVO ENTRE ARMADILHAS LUMINOSAS À BASE DE DIODOS EMISSORES DE LUZ E OUTROS MÉTODOS DE CAPTURA DE MOSQUITOS DO GÊNERO Anopheles (DIPTERA: CULICIDAE) - COSTA NETA, Benedita Maria (2023)
Anopheline mosquitoes are insects of medical importance, as the females of some species are responsible for transmitting the malarial genus Plasmodium. Vector monitoring constitutes one of the main tools in entomological surveys. The use of LED (Light-Emitting diode)-based light traps has been shown to be effective in capturing insect vectors, such as the Silva trap, a passive light trap designed for capturing anopheline mosquitoes. The aim of this study was to evaluate the efficiency of LED-based light traps with other trapping methods in malaria vectors surveillance. This study was carried out in two distinct regions: in the municipality of Chapadinha-MA and in the municipality of Macapá-AP. In the municipality of Chapadinha the research was divided in two moments. In the first, traps were deployed from 6:00 pm to 7:00 pm and from 7:00 pm to 6:00 am, and in the second moment, mosquitoes were collected at 20- minute intervals from 6:00 pm to 7:00 pm, totaling three intervals. In the study carried out in the municipalities of Macapá and Chapadinha, the traps was placed between 6:00 pm and 6:00 am. The Silva trap, CDC light traps and BG-Pro traps were used in these studies. 2815 mosquitoes were captured in the first study, distributed in nine species. The two most frequent species were Anopheles triannulatus and An. argyritarsis. It was observed that anopheline flight activity was not influenced by the lunar phase. Mosquitoes were most active in the first hour after sunset, especially during the nautical twilight period. In the second study, 2122 individuals were captured, distributed in 12 species. The most common species was An. triannulatus, accounting for 86.3% of the individuals. The Silva trap was efficient in capturing anophelines and captured more individuals compared to the BG-pro trap. Therefore, by developing new capture methods that can be used in studies to understand the behavior and pattern of flight activity of anopheline mosquitoes can be a way to guide strategies and measures to control vector species in endemic areas.